2018
DOI: 10.1021/acsami.7b18533
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Metal–Insulator Transition Performance in Scalable Vanadium Dioxide Thin Films Prepared Using a Moisture-Assisted Chemical Solution Approach

Abstract: Vanadium dioxide (VO) is a strong-correlated metal-oxide with a sharp metal-insulator transition (MIT) for a range of applications. However, synthesizing epitaxial VO films with desired properties has been a challenge because of the difficulty in controlling the oxygen stoichiometry of VO , where x can be in the range of 1< x < 2.5 and V has multiple valence states. Herein, a unique moisture-assisted chemical solution approach has been developed to successfully manipulate the oxygen stoichiometry, to significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 47 publications
(107 reference statements)
2
34
1
Order By: Relevance
“…However, the sol-gel method (or chemical solution) can conveniently modulate the oxygen stoichiometry in vanadium oxide. In previous work, a VO 2 thin film with enhanced MIT properties was synthesized by using a moisture-assisted chemical solution method [112]. In order to obtain high performance VO 2 films, it is very important to prevent the formation of V 5+ or V 3+ during the growth process.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…However, the sol-gel method (or chemical solution) can conveniently modulate the oxygen stoichiometry in vanadium oxide. In previous work, a VO 2 thin film with enhanced MIT properties was synthesized by using a moisture-assisted chemical solution method [112]. In order to obtain high performance VO 2 films, it is very important to prevent the formation of V 5+ or V 3+ during the growth process.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…The detailed growth process has been reported in our previous work. [39] The pure VO 2 films deposited on Al 2 O 3 substrates have a thickness of about 120 nm. The schematic diagram of the composite film is shown in figure 1(a).…”
Section: Eeperimentsmentioning
confidence: 99%
“…VO 2 films can be patterned by standard photolithography and wet etching technique, but these methods are complex. In this paper, VO 2 films were deposited on sub-wavelength metallic grating structures by the polymer assisted deposition (PAD) method [37][38][39][40]. The atomic force microscopy images revealed that the thickness of VO 2 films formed periodic height fluctuations and the fluctuation height increased with the increase of grating period.…”
Section: Introductionmentioning
confidence: 99%
“…When a mica substrate is thinned down to about few micrometers, the VO 2 /mica film becomes flexible, as shown in Figure S1 in the Supporting Information. The A g and B g vibration modes in the Raman spectrum (Figure S2, Supporting Information) reveal that the VO 2 film is an insulating monoclinic phase with space group P 2 1 / c (the M1 phase) at 298 K . Figure S3 in the Supporting Information shows the X‐ray diffraction (XRD) θ − 2θ scan of the VO 2 /mica film, and only the VO 2 (020) and (040) peaks, along with the mica (00 n ) ( n = 1, 2, 3, ..., 8) peaks are observed, indicating that the VO 2 film is of high purity and without other orientations.…”
Section: Compilation Of Optical Trigger Threshold Fth and Thz Field Mmentioning
confidence: 99%